The myth of judicial independence - McConville, Michael; Marsh, Luke (Oxford : Oxford University Press, 2020)
Through an examination of the history of the rules that regulate police interrogation (the Judges' Rules) in conjunction with plea bargaining and the Criminal Procedure Rules, this volume explores the 'Westminster Model' under which three arms of the State (parliament, the executive, and the judiciary) operate independently of one another. It reveals how policy was framed in secret meetings with the executive which then actively misled parliament in contradiction to its ostensible formal relationship with the legislature.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 23, 2020).
Keywords: Judicial independence -- Great Britain; Separation of powers -- Great Britain